Galectins as Master Regulators of Gastric Cancer Progression - Bojan Stojanovic; Ivan Jovanovic; Milica Dimitrijevic Stojanovic; Bojan Milosevic; Marko Spasic; Bojana S. Stojanovic; Stefan Jakovljevic; Nenad Zornic; Danijela Jovanovic; Jelena Nesic; Milan Paunovic; Ivan Radosavljevic; et al. (Cells)
Gastric cancer remains a major global health challenge, largely due to its biological heterogeneity and limited treatment options for advanced stages. Among the numerous molecular players involved in its pathogenesis, galectins—β-galactoside-binding lectins—have emerged as key modulators of tumor behavior. These multifunctional proteins influence diverse processes including cell proliferation, invasion, immune evasion, stromal remodeling, and therapy resistance. Recent advances in experimental and clinical research have shed light on the complex roles of galectin family members—particularly Galectin-1, -3, and -9—in shaping the tumor microenvironment and driving disease progression. This review highlights the current understanding of galectin biology in gastric cancer, with emphasis on their structural characteristics, cellular localization, functional diversity, and translational relevance. By synthesizing insights from molecular studies and clinicopathological observations, we explore the potential of galectins as biomarkers and therapeutic targets in the evolving landscape of gastric cancer research.